2009
DOI: 10.1007/s00423-009-0532-6
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative adjuncts in surgery for primary hyperparathyroidism

Abstract: Literature review provides the basis for clear recommendations on the use of intraoperative PTH at surgery for PHPT. There is little evidence to support the use of RGP, MB, routine frozen section, and intraoperative neuromonitoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
48
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 125 publications
2
48
0
3
Order By: Relevance
“…However, randomized studies show that in patients with positive Tc-MIBI scintigraphy, there is no added value to support the use of intraoperative iPTH measurement. 1 In fact, our current study revealed that in all cases with a positive Tc-MIBI scan, iPTH levels are decreased after the removal of a single adenoma. These results are compatible with those of previous studies that report that even without iPTH measurements, radioguided surgery results in an excellent cure rate, at least in selected cases of single adenomas.…”
Section: Discussionsupporting
confidence: 46%
See 3 more Smart Citations
“…However, randomized studies show that in patients with positive Tc-MIBI scintigraphy, there is no added value to support the use of intraoperative iPTH measurement. 1 In fact, our current study revealed that in all cases with a positive Tc-MIBI scan, iPTH levels are decreased after the removal of a single adenoma. These results are compatible with those of previous studies that report that even without iPTH measurements, radioguided surgery results in an excellent cure rate, at least in selected cases of single adenomas.…”
Section: Discussionsupporting
confidence: 46%
“…Some studies also recommend the use of intraoperative iPTH assay for multigland disease. 1,21,22 The iPTH assay can reliably be used for patients with multigland disease with an accuracy similar to that shown for single-adenoma cases. 21,22 The Tc-MIBI scan is not specific for parathyroid tissue, and thyroid nodules also accumulate Tc-MIBI.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…110 In this case intra operative measurement of PTH serum level gives the surgeon the certainty of having removed the pathological gland responsible for PHPT. 111 Recent technological developments, including the option of intra operative measurement of PTH, endoscopic technique and mainly the utilization of intra operative gamma probe, justify the success of minimally invasive surgical procedures. [112][113][114] The mini invasive procedures are summarized in Table 4.…”
Section: Surgical Treatmentmentioning
confidence: 99%